Brighter than the sun - Quinn, Julia, 1970-.; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1997)
Charles Wycombe, Earl of Billington, needs a bride to keep his inheritance and Miss Eleanor Lyndon needs a home to escape her father's fiancee, but their platonic union of mutual convenience is soon threatened by calamity, misunderstanding, and passion.
Keywords: Inheritance and succession -- Fiction; Nobility -- Fiction; Man-woman relationships -- Fiction; Kent (England) -- Fiction; Love stories; Historical fiction